Non-alcoholic fatty liver disease: from understanding risk factors to finding optimal treatment regimens: A review - Daria A. Teplyuk; Aliya A. Kaisina; Shabnam I. Ibragimova; Afina A. Bestavashvili; Irina O. Tinkova; Evgeniia Iu. Pashkova; Jamilya A. Kaibullayeva; Alexander V. Nersesov; Chavdar S. Pavlov (ZAO "Consilium Medicum", 2023)
Non-alcoholic fatty liver disease (NAFLD) is now a major risk factor for death among patients with liver disease. Currently, drugs that primarily affect surrogate markers of NAFLD are available. However, none of these drugs showed a significant effect on the course of steatohepatitis and fibrogenesis. The search for the most relevant lifestyle modification programs is still a priority in comprehensive treatment. A clinical case of follow-up of a comorbid patient is presented. Despite comprehensive treatment, disease regression was not achieved. NAFLD therapy remains a relevant issue. Finding new ways to affect the NAFLD course and individualize treatment approaches is necessary.